Food throughput time in European Wigeon Anas penelope and other grazing waterfowl - Mayhew, Peter W; Houston, David C (Wildfowl, 1993)
The mean retention time for food passing through the gut of European Wigeon was determined, using a ruthenium isotope as an inert marker, at 74 minutes. This was compared with other published figures for larger grazing geese. The data suggest a relationship between body mass and retention time in grazing wildfowl, although this is not significant, with small species passing food through their guts proportionally more slowly than large ones. This should allow them to sustain a high digestive efficiency.